IMPLEMENTASI FRAMEWORK FLUTTER UNTUK PENGADUAN MAHASISWA UNIVERSITAS XYZ - Angghy Nur Septian (Balitbangda Provinsi Lampung, 2021)
Student complaints are a process for conveying information or complaints that are felt by students and submitted by students about campus academic services whose performance is unsatisfactory. Student complaints are needed in a university to improve and improve the performance and quality of the university. At XYZ University there is no system for students to submit complaints, every semester students only fill out a questionnaire that has been provided by the campus, but there are still students who are not satisfied with the contents of the questionnaire. The solution to this problem is to create a system using a framework, namely flutter, which later can be used by students to submit complaints easily, and can submit these complaints at any time. The campus can also make complaints that have been submitted as evaluation materials to make it even better.